Long-term toxicity of reduced graphene oxide nanosheets: Effects on female mouse reproductive ability and offspring development. (June 2015) - Xu, Shun; Zhang, Zheyu; Chu, Maoquan
Abstract: Reduced graphene oxide (rGO) nanosheets have emerged as novel materials for cancer therapeutics. Their toxicity has attracted much attention since these nanomaterials may have great potential for clinical cancer treatment. Here we report the influence of rGO exposure on female mouse reproductive ability and offspring development. Mouse dams were injected with small or large rGO nanosheets at different doses and time points, pre- or post-fertilization. The sex hormone levels of adult female mice did not significantly change compared with the control group after intravenous injection with either small or large rGO, even at a high dose (25 mg/kg). Mouse dams could produce healthy offspring after treatment with rGO nanosheets before pregnancy and at an early gestational stage (∼6 days). Despite the successful delivery of offspring, malformed fetuses were found among rGO-injected dam litters. All mice had abortions when injected with low (6.25 mg/kg) or intermediate (12.5 mg/kg) doses at a late gestational stage (∼20 days); the majority of pregnant mice died when injected with the high dose of rGO at this stage of pregnancy. Interestingly, all surviving rGO-injected mouse mothers gave birth to another litter of healthy pups. The results presented in this work are important for a deeper understanding of the toxicity of rGO nanosheets on female reproductivity and their offspring development.